Exploring methods of quantity measurement for heritage conservation works - Ali, Maisarah; Ibrahim, Md Najib; Mohd Yunus, Rodzyah; Yahya, Mohamad Ridzuan; Ismail, Faridah; Mohd. Din, Azrin; Ibrahim, Mohd Shariffuddin (2016)
Heritage is very important to a society and country as it reflects the true identity of the country and creates a sense of wonder about the people and culture that produced it. Unlike new building works, the heritage conservation works are unique and distinctive individually, which do not have a precedent case to study. The existence of complexity and uncertainty elements throughout the process can disrupt the traditional requirements for price certainty, a known date of delivery and acknowledged quality standards. Therefore, this research is intended to identify common parameters to be considered in the quantity measurement of conservation works. The methodology adopted is semi structured interview and content analysis. The common parameters for quantity measurement of heritage conservation works are Historical Architecture Building Survey (HABS), Heritage Impact Assessment (HIA) (for certain projects), dilapidation survey, laboratory test and scientific studies, sample study, employment of conservation professional in the contractor’s team.